The Structural Model of Educational Self-regulation Based on Learning Strategies and Attributional Styles by the Mediator of Achievement Motivation Among Secondary High School Students in Sari in 2017-2018 - Shirdel, Kheironesa; Fakhri, Mohammad Kazem; Mirzaeyan, Bahram (International Clinical Neuroscience Journal, 2018)
Background: Achievement motivation is one of the critical variables that predict educational achievement and success in the future. Therefore, the identification of effective factors upon achievement motivation may be one of the basic subjects in education. The present study aimed to evaluate the structural model of educational self-regulation based on learning strategies by the mediator of achievement motivation among students. Methods: The present study was correlation research with structural equation modeling (SEM). The statistical universe of this study consisted of all boy and girl students at secondary high schools in 2017-2018. The multistep random cluster sampling selected 375 (215 girls and 160 boys). Data gathered by the Bouffard educational self-regulation questionnaire, learning strategies questionnaire, attributional style questionnaire, and Herman’s achievement motivation questionnaire. Data analysis gathered by path analysis and structural equations with Lisrel 8.80 software. Results: The research results indicated the direct effects of learning strategies and attributional styles upon achievement motivation (P < 0.05). Also, model fitting indicated indirect effects of learning strategies and attributional styles by achievement motivation upon students learning self-regulation (P < 0.01). Conclusion: Research results indicate that self-regulation learning strategies are educational. The teaching of these strategies is effective in increasing internal attribution style for positive events and decreasing this style for adverse events among students.